The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.15252/embr.202357042
|View full text |Cite
|
Sign up to set email alerts
|

Blood flow diverts extracellular vesicles from endothelial degradative compartments to promote angiogenesis

Benjamin Mary,
Nandini Asokan,
Katerina Jerabkova‐Roda
et al.

Abstract: Extracellular vesicles released by tumors (tEVs) disseminate via circulatory networks and promote microenvironmental changes in distant organs favoring metastatic seeding. Despite their abundance in the bloodstream, how hemodynamics affect the function of circulating tEVs remains unsolved. We demonstrated that efficient uptake of tEVs occurs in venous endothelial cells that are subjected to hemodynamics. Low flow regimes observed in veins partially reroute internalized tEVs toward non‐acidic and non‐degradativ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 75 publications
(113 reference statements)
0
2
0
Order By: Relevance
“…MemBright has been widely adopted by the extracellular vesicles community 51 to track extracellular vesicles both in vitro or in vivo in hippocampal 63 or cortical neurons, 79 zebrafish, 62,67,72 breast cancer cells or tumours, 66,71,80 myotubes, 82 and red blood cells. 74,76 Particle size distribution and zeta potential analysis of EVs derived from A375 cells using nanoparticle tracking analysis (NTA) showed that EVs labeled before and after labeling by MemBright have almost no change in size and only a slight shift of zeta potential.…”
Section: Imaging Extracellular Vesiclesmentioning
confidence: 99%
“…MemBright has been widely adopted by the extracellular vesicles community 51 to track extracellular vesicles both in vitro or in vivo in hippocampal 63 or cortical neurons, 79 zebrafish, 62,67,72 breast cancer cells or tumours, 66,71,80 myotubes, 82 and red blood cells. 74,76 Particle size distribution and zeta potential analysis of EVs derived from A375 cells using nanoparticle tracking analysis (NTA) showed that EVs labeled before and after labeling by MemBright have almost no change in size and only a slight shift of zeta potential.…”
Section: Imaging Extracellular Vesiclesmentioning
confidence: 99%
“…Third, EVs have a remarkable capacity to transverse biological barriers, such as bloodbrain barriers or endothelial barriers. [146][147][148] Although this feature holds significant therapeutic implications, how EVs accomplish this feat is still being elucidated, and whether this is true in higher primates is being debated and in humans, unknown. Proposed mechanisms include transcytosis (internalized by endothelial cells and subsequently released across the barrier) and EVmediated inflammation that disrupts tight junctions between endothelial cells and compromises barrier permeability.…”
Section: Challenges In Ev Therapeuticsmentioning
confidence: 99%